2011
DOI: 10.1002/j.2048-7940.2011.tb00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Art in Alzheimer's Care: Promoting Well-Being in People with Late-Stage Alzheimer's Disease

Abstract: The purpose of this qualitative study was to explore the responses of people with late‐stage Alzheimer's disease (AD) to a creative bonding intervention (CBI). The CBI consisted of simple art activities. Guided by Reed's self‐transcendence theory, research questions were “Will persons with late‐stage AD show evidence of self‐transcendence during the CBI?” and “Will persons with late‐stage AD show evidence of well‐being during the CBI?” Twelve CBI sessions, documented by videotape and field notes, were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 29 publications
1
27
0
2
Order By: Relevance
“…15,21,[37][38][39] An intervention study using reminiscence among older women in assisted living also found a non-significant trend toward increased ST and decreased depression. Other studies using group support and bonding to increase ST and associated positive effects among women with breast cancer, persons with Alzheimer's disease, and caregivers of elders with dementia have demonstrated non-significant trends toward increased ST and provided qualitative evidence supporting the potential to effectively increase ST. 12,13,20,41,42 However, there is scant evidence of interventions showing statistically significant increases in ST and related positive outcomes, largely due to the small number of quantitative studies and small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,21,[37][38][39] An intervention study using reminiscence among older women in assisted living also found a non-significant trend toward increased ST and decreased depression. Other studies using group support and bonding to increase ST and associated positive effects among women with breast cancer, persons with Alzheimer's disease, and caregivers of elders with dementia have demonstrated non-significant trends toward increased ST and provided qualitative evidence supporting the potential to effectively increase ST. 12,13,20,41,42 However, there is scant evidence of interventions showing statistically significant increases in ST and related positive outcomes, largely due to the small number of quantitative studies and small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…People with late-stage Alzheimer's disease exposed to a creative bonding intervention displayed evidence of ST and well-being. 42 Caregivers of elders with dementia who participated in a poetry writing intervention found female caregivers were lower in ST and resilience, and higher in depressive symptoms and burden, but older caregivers scored higher than younger caregivers. 20 Subthemes identified using grounded theory included greater PROMOTING SELF-TRANSCENDENCE 6 acceptance, empathy, self-awareness, reflection, creativity, and helping others.…”
mentioning
confidence: 99%
“…The AI was developed from findings in previous studies (7)(8)(9)(10). The AI consists of three brief, user-friendly art activities: a monoprint, a ribbon gem, and a self-image portrait.…”
Section: Sample Setting and Description Of The Aimentioning
confidence: 99%
“…Similar activities promoted health and well-being in vulnerable groups but have not yet been tested with hospitalized veterans [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Art-based creative activities have been used as complimentary therapy in rehabilitation as a means for promoting personal expression, intellectual, aesthetic, and social growth, as well as in recognizing and supporting affective concerns, thus improving health and well-being (Malchiodi, 2000). Clinical groups where creative arts have been applied include those with chronic pain (Kelly, Cudney, & Weinert, 2012), stroke (Baumann, Peck, Collins, & Eades, 2013;B€ azner & Hennerici, 2007;Beesley, White, Alston, Sweetapple, & Pollack, 2011;Gonen & Soroker, 2000), Alzheimer's disease (Chancellor, Duncan, & Chatterjee, 2014;Walsh et al, 2011), and cancer (e.g., Ho, 2005;Visser & Hoog, 2008). The value of creative arts in promoting holistic well-being has been gradually recognized in the rehabilitation or recovery from major life-altering illnesses (Kelly et al, 2012;Malchiodi, 2000;Rancour & Barrett, 2011).…”
Section: Introductionmentioning
confidence: 98%